Praktik Kerja Dokter Laki-laki dalam Menangani Pasien Perempuan Perspektif Maqashid Syariah - Nur Laily Himami Habsawati (Rechtenstudent, 2020)
In the medical world, interactions between doctors and patients are certain to happen. To examine a patient, sometimes a doctor has to touch the patient's body, perform an injection or injection, to a cesarean section, which is certainly the most sensitive part of the body. And it is not uncommon for medical workers of the opposite sex who perform these actions. Meanwhile in Indonesia currently the percentage of male and female doctors is not balanced, where male doctors are more dominant than female doctors, even for certain specialties, such as obstetricians, now there are many male doctors, even more dominant than doctors. girls. The fact that patients who want to seek treatment and use health services are mostly male doctors. So that in this study will discuss how the handling of male doctors in treating female patients based on the perspective of Maqashid Syariah. Nurturing the soul is one of the basic sub-materials of Maqashid Sharia, this point is of concern in the discussion of this research. The Maqashid Sharia itself includes five basic aspects, namely the maintenance of religion, soul, mind, descent and property. And this research uses qualitative research to produce descriptive data.